Development of Advanced Space Technologies and Systems as the Basis of Russia’s Technological Sovereignty - A. E. Sergeeva (Мир новой экономики, 2025)
The relevance of this study is driven by the critical importance of developing high-tech and knowledge-intensive industries for the Russian economy. The article argues that scientific research and development in the space industry serve as both an indicator of Russia’s scientific and technological progress and a subject of international competition. The results of space activities are in demand by a wide range of consumers. Space technologies are used as a tool for solving governmental and municipal management tasks. Services based on Earth remote sensing data from space have become an indispensable source of timely and relevant information for ensuring the operation of various sectors of the national economy. The study highlights that achieving technological sovereignty and leadership requires a comprehensive approach to the development and implementation of high-tech products and services, considering the mutually beneficial cooperation between the state and private companies. The author presents international experiences in implementing open data policies in the space sector, analyzes Russia’s position in the global Earth remote sensing market, and discusses promising space industry projects. The implementation of these projects could serve as one of the first examples of applying the public-private partnership mechanism in Russia’s space sector.